Can Toxoplasma gondii Pave the Road for Dementia? - Enas A. El Saftawy; Noha M. Amin; Rania M. Sabry; Noha El-Anwar; Rania Y. Shash; Eman H. Elsebaie; Rita M. Wassef (Journal of Parasitology Research)
Dementia is an ominous neurological disease. Scientists proposed a link between its occurrence and the presence of Toxoplasma gondii (T. gondii). The long-term sequels of anti-Toxoplasma premunition, chiefly dominated by TNF-α, on the neurons and their receptors as the insulin-like growth factor-1 receptor (IGF-1R), which is tangled in cognition and synaptic plasticity, are still not clear. IGF-1R mediates its action via IGF-1, and its depletion is incorporated in the pathogenesis of dementia. The activated TNF-α signaling pathway induces NF-κβ that may induce or inhibit neurogenesis. This study speculates the potential impact of anti-Toxoplasma immune response on the expression of IGF-1R in chronic cerebral toxoplasmosis. The distributive pattern of T. gondii cysts was studied in association with TNF-α serum levels, the in situ expression of NF-κβ, and IGF-1R in mice using the low virulent ME-49 T. gondii strain. There was an elevation of the TNF-α serum level (p value ≤ 0.004) and significant upsurge in NF-κβ whereas IGF-1R was of low abundance (p value < 0.05) compared to the controls. TNF-α had a strong positive correlation with the intracerebral expression of NF-κβ (r value ≈ 0.943, p value ≈ 0.005) and a strong negative correlation to IGF-1R (r value -0.584 and -0.725 for area% and O.D., respectively). This activated TNF-α/NF-κβ keeps T. gondii under control at the expense of IGF-1R expression, depriving neurons of the effect of IGF-1, the receptor’s ligand. We therefore deduce that T. gondii immunopathological reaction may be a road paver for developing dementia.